Performance Characteristics of the Magnetic Constrained Layer Damping - A. Baz; S. Poh (Shock and Vibration)
A new class of surface damping treatment is proposed to provide effective means for attenuating undesirable structural vibrations. The proposed treatment relies in its operation on the use of smart damping treatments which consist of integrated arrays of constrained visco-elastic damping layers that are controlled passively by a specially arranged network of permanent magnets. The interaction between the magnets and the visco-elastic layers aims at enhancing the energy dissipation characteristics of the damping treatments. In this manner, it would be possible to manufacture structures that are light in weight which are also capable of meeting strict constraints on structural vibration when subjected to unavoidable disturbances.